The Study of Synergistic Changes in Extreme Cold and Warm Events in the Sanjiang Plain - Baoqi Li; Yanyu Chi; Hang Zhou; Shaoxiong Zhang; Yao Lu (Atmosphere)
Extreme climate events are occurring frequently under global warming. Previous studies primarily focused on isolated extreme climate events, whereas research on the synergistic changes between extreme cold (EC) and extreme warm (EW) events remains limited. This study conducted trend, correlation, and dispersion analyses on EC and EW, as well as their synergistic changes, in the Sanjiang Plain from 1960 to 2019, using inverse distance weighting, statistical methods, and the Mann–Kendall test. The results indicated that cold-to-warm (C2W) and warm-to-cold (W2C) events were significantly and positively correlated with elevation, with correlation coefficients (r) of 0.76 and 0.84, respectively. Meanwhile, C2W showed a significant negative correlation with latitude (r = −0.55), while W2C also exhibited a significant negative correlation with latitude (r = −0.71). However, there was a significant positive correlation between (EC) and latitude (r = 0.65). After 1980, both the declining trend of EC and the increasing trend of EW slowed down, and the trends in C2W and W2C changed from decline to increase. The dispersion of EC and EW shows an increasing trend, while the dispersion of C2W and W2C exhibits a decreasing trend. This study provides important references for studying temperature fluctuations and addressing extreme climate changes.